Students’ perceptions of using board game to learn idiom: a study on Idioms Hunter - Journey Beyond Words / Muhammad Irfan Mokhtar ... [et al.] - Mokhtar, Muhammad Irfan; Khairol Anuar, Nur Alyani; Abdul Talib, Nur Syuhada Iman; Hariulnizam, Wardina Zalia; Khairul Faizi, Alif Hakeem (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
English literacy among ESL learners normally centres around the capability of learners to communicate in English competently. However, it is often a problem for ESL learners when the communication involves the use of idioms. Idioms are a figurative language where meaning cannot be taken literally. However, idioms rarely being included in the lesson of English, as many teachers choose to let learners learn them on their own. Learning idioms can be a dreadful experience for ESL learners as idioms are commonly used by native speakers and not oftenly used by ESL learners. Thus, a board game called ‘Idioms Hunter: Journey Beyond Words’ was designed to help ESL learners to acquire a better knowledge of idioms. This board game was inspired by the famous snake and ladder board game. However, ‘Idioms Hunter’ will give players a better experience as they will be playing to solve the mission by answering questions on idioms. This educational game will work as a stimulant to catch and captivate students’ attention in learning idioms.